\ x_{1}=1, \ x_{2}=\frac{c}{a}\\ 2+(-1)+(-1)=0\\ x_{1}=1, \ x_{2}=\frac{-1}{2}=-\frac{1}{2}\\ 2x^{2}-x-1=2(x-1)(x+\frac{1}{2})\\\\ " alt="\frac{(-x^{2}-3x-2)}{x^{2}+4x+4}-\frac{2x^{2}-x-1}{x-1}\\\\ 1. \ -x^{2}-3x-2=0\\ D = b^{2}-4ac=(-3)^{2}-4\cdot (-1)\cdot (-2)=9-8=1\\ x_{1,2}=\frac{-b+/-\sqrt{D}}{2a}\\ x_{1}=\frac{3+1}{2\cdot (-1)}=\frac{4}{-2}=-2\\ x_{2}=\frac{3-1}{2\cdot (-1)}=\frac{2}{-2}=-1\\ -x^{2}-3x-2=-(x+1)(x+2)\\\\ 2. \ x^{2}+4x+4= (x+2)^{2}\\\\ 3. \ 2x^{2}-x-1=0\\ a+b+c = 0 \ => \ x_{1}=1, \ x_{2}=\frac{c}{a}\\ 2+(-1)+(-1)=0\\ x_{1}=1, \ x_{2}=\frac{-1}{2}=-\frac{1}{2}\\ 2x^{2}-x-1=2(x-1)(x+\frac{1}{2})\\\\ " align="absmiddle" class="latex-formula">
![\frac{-(x+1)(x+2)}{(x+2)^{2}}-\frac{2(x-1)(x+\frac{1}{2})}{x-1}=-\frac{(x+1)(x+2)}{(x+2)^{2}}-\frac{2(x-1)(x+\frac{1}{2})}{x-1}=\\ =-\frac{x+1}{x+2}-2(x+\frac{1}{2}}) \ | \cdot (x+2)=-(x+1)-2(x+\frac{1}{2})(x+2)=\\ =-x-1-2(x^{2}+2x+\frac{1}{2}x+1)=-x-1-2(x^{2}+\frac{5}{2}+1)=\\ =-x-1-2x^{2}-5x-2=-2x^{2}-6x-3\\\\ -2x^{2}-6x-3=0\\ D = (-6)^{2}-4\cdot (-2)\cdot (-3)=36-24=12\\ x_{1}=\frac{6+\sqrt{12}}{-4}=-\frac{6+2\sqrt{3}}{4}=-\frac{2(3+\sqrt{3})}{4}=-\frac{3+\sqrt{3}}{2}\\ \frac{-(x+1)(x+2)}{(x+2)^{2}}-\frac{2(x-1)(x+\frac{1}{2})}{x-1}=-\frac{(x+1)(x+2)}{(x+2)^{2}}-\frac{2(x-1)(x+\frac{1}{2})}{x-1}=\\ =-\frac{x+1}{x+2}-2(x+\frac{1}{2}}) \ | \cdot (x+2)=-(x+1)-2(x+\frac{1}{2})(x+2)=\\ =-x-1-2(x^{2}+2x+\frac{1}{2}x+1)=-x-1-2(x^{2}+\frac{5}{2}+1)=\\ =-x-1-2x^{2}-5x-2=-2x^{2}-6x-3\\\\ -2x^{2}-6x-3=0\\ D = (-6)^{2}-4\cdot (-2)\cdot (-3)=36-24=12\\ x_{1}=\frac{6+\sqrt{12}}{-4}=-\frac{6+2\sqrt{3}}{4}=-\frac{2(3+\sqrt{3})}{4}=-\frac{3+\sqrt{3}}{2}\\](https://tex.z-dn.net/?f=%5Cfrac%7B-%28x%2B1%29%28x%2B2%29%7D%7B%28x%2B2%29%5E%7B2%7D%7D-%5Cfrac%7B2%28x-1%29%28x%2B%5Cfrac%7B1%7D%7B2%7D%29%7D%7Bx-1%7D%3D-%5Cfrac%7B%28x%2B1%29%28x%2B2%29%7D%7B%28x%2B2%29%5E%7B2%7D%7D-%5Cfrac%7B2%28x-1%29%28x%2B%5Cfrac%7B1%7D%7B2%7D%29%7D%7Bx-1%7D%3D%5C%5C+%3D-%5Cfrac%7Bx%2B1%7D%7Bx%2B2%7D-2%28x%2B%5Cfrac%7B1%7D%7B2%7D%7D%29+%5C+%7C+%5Ccdot+%28x%2B2%29%3D-%28x%2B1%29-2%28x%2B%5Cfrac%7B1%7D%7B2%7D%29%28x%2B2%29%3D%5C%5C+%3D-x-1-2%28x%5E%7B2%7D%2B2x%2B%5Cfrac%7B1%7D%7B2%7Dx%2B1%29%3D-x-1-2%28x%5E%7B2%7D%2B%5Cfrac%7B5%7D%7B2%7D%2B1%29%3D%5C%5C+%3D-x-1-2x%5E%7B2%7D-5x-2%3D-2x%5E%7B2%7D-6x-3%5C%5C%5C%5C+-2x%5E%7B2%7D-6x-3%3D0%5C%5C+D+%3D+%28-6%29%5E%7B2%7D-4%5Ccdot+%28-2%29%5Ccdot+%28-3%29%3D36-24%3D12%5C%5C+x_%7B1%7D%3D%5Cfrac%7B6%2B%5Csqrt%7B12%7D%7D%7B-4%7D%3D-%5Cfrac%7B6%2B2%5Csqrt%7B3%7D%7D%7B4%7D%3D-%5Cfrac%7B2%283%2B%5Csqrt%7B3%7D%29%7D%7B4%7D%3D-%5Cfrac%7B3%2B%5Csqrt%7B3%7D%7D%7B2%7D%5C%5C+)
![x_{2}=\frac{6-\sqrt{12}}{-4}=-\frac{6-2\sqrt{3}}{4}=-\frac{2(3-\sqrt{3})}{4}=-\frac{3-\sqrt{3}}{2}\\\\ -2x^{2}-6x-3=-2(x+\frac{3+\sqrt{3}}{2})(x+\frac{3-\sqrt{3}}{2}) x_{2}=\frac{6-\sqrt{12}}{-4}=-\frac{6-2\sqrt{3}}{4}=-\frac{2(3-\sqrt{3})}{4}=-\frac{3-\sqrt{3}}{2}\\\\ -2x^{2}-6x-3=-2(x+\frac{3+\sqrt{3}}{2})(x+\frac{3-\sqrt{3}}{2})](https://tex.z-dn.net/?f=x_%7B2%7D%3D%5Cfrac%7B6-%5Csqrt%7B12%7D%7D%7B-4%7D%3D-%5Cfrac%7B6-2%5Csqrt%7B3%7D%7D%7B4%7D%3D-%5Cfrac%7B2%283-%5Csqrt%7B3%7D%29%7D%7B4%7D%3D-%5Cfrac%7B3-%5Csqrt%7B3%7D%7D%7B2%7D%5C%5C%5C%5C+-2x%5E%7B2%7D-6x-3%3D-2%28x%2B%5Cfrac%7B3%2B%5Csqrt%7B3%7D%7D%7B2%7D%29%28x%2B%5Cfrac%7B3-%5Csqrt%7B3%7D%7D%7B2%7D%29)